Comparative genomics of Hox and ParaHox genes among major lineages of Branchiopoda with emphasis on tadpole shrimps - Nicolini, Filippo; Martelossi, Jacopo; Forni, Giobbe; Savojardo, Castrense; Mantovani, Barbara; Luchetti, Andrea (Frontiers in Ecology and Evolution, 2023)
Hox and ParaHox genes (HPHGs) are key developmental genes that pattern regional identity along the anterior-posterior body axis of most animals. Here, we identified HPHGs in tadpole shrimps (Pancrustacea, Branchiopoda, Notostraca), an iconic example of the so-called “living fossils'', and performed a comparative genomics analysis of HPHGs and the Hox cluster among major branchiopod lineages. Notostraca possess the entire Hox complement and the Hox cluster seems to be split into two different subclusters, although we were not able to support this finding with chromosome-level assemblies. However, the genomic structure of Hox genes in Notostraca appears more derived than that of Daphnia spp., which instead retains the plesiomorphic condition of a single compact cluster. Spinicaudata and Artemia franciscana show instead a Hox cluster subdivided across two or more genomic scaffolds with some orthologs either duplicated or missing. Yet, branchiopod HPHGs are similar among the various clades in terms of both intron length and number, as well as in their pattern of molecular evolution. Sequence substitution rates are in fact generally similar for most of the branchiopod Hox genes and the few differences we found cannot be traced back to natural selection, as they are not associated with any signals of diversifying selection or substantial switches in selective modes. Altogether, these findings do not support a significant stasis in the Notostraca Hox cluster and further confirm how morphological evolution is not tightly associated with genome dynamics.